A) (3m – 2) (2m – 1) =

b) (4z2 – 1)(z2 + 5) =

c) (5ab2 + 4b3) (3ab3 – 4a2) =

d) (8a2 – 3ab) (3a2 – ab) =

e) (7x3 – xy) (-2x2y2 + 5xy) =

f) (x2 + 2y – 5x) (2x2 – 3y) =

g) (a2 – 5ab + 3b2) (a2 – 2ab) =

h) (x – y)2 =

i) (-5x + 3)2 =

3

Odpowiedzi

2010-01-22T11:56:40+01:00
A) (3m – 2) (2m – 1) =6m²-3m-4m+2=6m²-7m+2

b) (4z2 – 1)(z2 + 5) =4z⁴+20z²-z²+5

c) (5ab2 + 4b3) (3ab3 – 4a2) =15ab⁶-20a²b²+12ab⁹-16a²b³

d) (8a2 – 3ab) (3a2 – ab) =24a⁴-8a³b-9a³b+3a²b²

h) (x – y)2 =x²-2xy+y²

i) (-5x + 3)2 =25x²-7x+9
2 4 2
Najlepsza Odpowiedź!
2010-01-22T12:01:44+01:00
A) (3m – 2) (2m – 1) = 5m2 - 3m - 4m + 2 = 5m2 - 7m + 2

b) (4z2 – 1)(z2 + 5) = 4z4 + 20z2 - z2 - 5 = 4z4 + 18z2 - 5

c) (5ab2 + 4b3) (3ab3 – 4a2) = 15a2b5 - 20a3b2 + 12ab6 - 16a2b3

d) (8a2 – 3ab) (3a2 – ab) = 24a4 - 8a3b - 9a3b + 3a2b2 = 24a4 - 17a3b + 3a2b2

e) (7x3 – xy) (-2x2y2 + 5xy) = - 14x5y2 + 35x4y + 2x3y3 - 5x2y2

h) (x – y)2 = x2 + y2

i) (-5x + 3)2 = 25x2 + 9

Pozdrawiam,
Buzzy ;-)
2 5 2
2010-01-22T12:07:22+01:00
A) (3m – 2) (2m – 1) = 6m² -5m+3
b) (4z2 – 1)(z2 + 5) =4(z2)²+20(z2)-5-z2
c) (5ab²+ 4b³) (3ab³ – 4a²) =15ab⁶+12b³×a³-4b³×4a³-20a²+5b²
d) (8a² – 3ab) (3a² – ab) =24a²-8a²×
g) (a2 – 5ab + 3b2) (a2 – 2ab) =2a²-a²×2ab-5ab×a²+10ab+3b²×a²-3b²×2ab
h) (x – y)2 =2x-2y
i) (-5x + 3)2 = -10x+6
2 4 2